New Allometric Scaling Relationships and Applications for Dose and Toxicity Extrapolation. (November 2014) - Cao, Qiming; Yu, Jimmy; Connell, Des
Allometric scaling between metabolic rate, size, body temperature, and other biological traits has found broad applications in ecology, physiology, and particularly in toxicology and pharmacology. Basal metabolic rate (BMR) was observed to scale with body size and temperature. However, the mass scaling exponent was increasingly debated whether it should be 2/3, 3/4, or neither, and scaling with body temperature also attracted recent attention. Based on thermodynamic principles, this work reports 2 new scaling relationships between BMR, size, temperature, and biological time. Good correlations were found with the new scaling relationships, and no universal scaling exponent can be obtained. The new scaling relationships were successfully validated with external toxicological and pharmacological studies. Results also demonstrated that individual extrapolation models can be built to obtain scaling exponent specific to the interested group, which can be practically applied for dose and toxicity extrapolations.